Frequency of Depression in Patients of Type 2 Diabetes Mellitus - Muhammad Ahsan Sana; Nouman Kashif; Khalid Azam (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of depression and associated risk factors in patients with type 2 diabetes mellitus.